International banking and foreign trade: being the lectures delivered at the Eighth International Banking Summer School, Christ Church, Oxford, September 1955 - Institute of Bankers (London: Published for the Institute of Bankers by Europa Publications, 1955)
These lectures were delivered before an audience of bankers from forty-four countries at the Eighth International banking summer school in September 1955. The problems of international trade and payments discussed at this year's school are among the most urgent of our time; their early solution is vital to the welfare of men and women throughout the world.
Bibliography: p. 71. Bibliographical references included in "Notes" (p. 201-204)
usc 28/09/2018
Loans
Keywords: Commerce; Currency question; Foreign exchange; Great Britain